Exploring the role of peer-assisted learning for professional preparation in recreation. Issue 1 (2nd January 2022) - Hutchinson, Susan; Woodford, Kimberley; Ellis, Allison; Hamilton-Hinch, Barbara; Stilwell, Christie; Manuel, Cassandra
ABSTRACT: In the recreation sector there is concern for ensuring that students and practitioners have adequate knowledge and skills to contribute to its growth and sustainability. While other researchers have identified the importance of personal attributes (i.e., 'soft' skills) for entry-level practitioners, there has been limited exploration of how peer assisted learning might contribute to preparing recreation students for their future professional practice. Recreation students from three different courses who were involved in a leisure education-based peer learning project participated in the study. Three themes were constructed to reflect students' perceptions: (1) benefits of peer learning for preparing for future practice, 2) practice for real life, and (3) factors impacting abilities to facilitate peer learning. The results are discussed in relation to the role of peer learning or mentoring in cultivating personal and professional growth and development in and for the recreation sector.